The effect of the information disclosure in the propensity of credit buying - Mette, Frederike Monika Budiner (2014)
The present study aimed to verify the effect of disclosure of credit terms in buying with in the propensity of individuals to consume this credit moderated by the debt literacy and the possibility of cash payment of the respondents. It was conducted an experiment with 3 scenarios for the disclosure of the condition in buying on credit. From the results presented through the tests it was shown that the greater the amount of information the greater propensity of consumption on credit. It was proved that the higher the level of debt literacy the lower the propensity to consume on credit.